Synthesis of Hydroxy-α-sanshool - Wu, Bo; Li, Kun; Toy, Patrick H. (Synlett, 2012)
The amide hydroxy-α-sanshool is responsible for the mild numbing sensation experienced when Sichuan (or Szechuan) peppercorns (huajiao) are eaten. It has been synthesized in six steps from simple commercially available starting materials using Wittig reactions as the key transformations for construction of the carbon skeleton. The penultimate synthetic intermediate was 2E,6Z,8E,10E-dodecatetraenoic acid, and its crystalline nature allowed it, and thus hydroxy-α-sanshool, to be purified to a very high level of stereochemical homogeneity.
Keywords: natural products; isomers; alkenes; Wittig reaction; aldehydes